Measuring Recovery in Parents Experiencing Mental Health Problems. (May 2019) - Thompson, Emma; Sheen, Jade; Maybery, Darryl
Parenting is a fundamental life domain with increasing evidence suggesting the parenting role has the capacity to inform and promote mental health recovery. Two reviews examined the current tools available to assess parenting in the context of recovery. Review one identified 35 quantitative measures of parenting used in interventions for parents with mental health problems. None of these measures appeared to consider parenting from a recovery orientation. Review two identified 25 measures of personal recovery; however, none appeared to consider the parenting role. Despite the fundamental life role of parenting, our ability to measure these constructs appears limited. Further research is warranted into the development of a measure of recovery that considers the parenting role.